Pengaruh Citra Perusahaan, Kualitas Layanan, Suku Bunga, dan Promosi terhadap Keputusan Pengambilan Kredit Pemilikan Rumah Pada PT. Bank Tabungan Negara (Persero) Tbk Kantor Cabang Gresik - Qusnul Dyah Novitasari; Roziana Ainul Hidayati (Jurnal Mahasiswa Manajemen, 2020)
This study aims to determine the Influence of Corporate Image, Service Quality, Interest Rates and Promotions on Decisions of Taking Home Ownership Loans (KPR) at PT. Bank Tabungan Negara (Persero) Tbk Gresik Branch Office. The sample in this study uses accidental sampling based on chance. The size of the sample used was 100 respondents. The analysis technique uses multiple regression analysis. Data collection techniques are using questionnaire. The results of this study indicate that corporate image influences credit decision making, Service Quality influences credit leverage decisions, Interest rates affect credit decision making, Promotion affects the decision to take home ownership loans (KPR) at PT. Bank Tabungan Negara (Persero) Tbk Gresik Branch Office.